Identification of ricin A-chain HLA class II-restricted epitopes by human T-cell clones - Tommasi, M (Blackwell Science Inc, 2001)
The identification of ricin toxin A-chain (RTA) epitopes and the molecular context in which they are recognized will allow strategies to be devised that prevent/suppress an anti-RTA immune response in patients treated with RTA-based immunotoxins. RTA-specific human T-cell lines and T-cell clones were produced by in vitro priming of PBMC. The T-cell clones used a limited set of Vβ chains (Vβ1, Vβ2 and Vβ8) to recognize RTA epitopes. The use of RTA deletion mutants demonstrated that T-cell lines and T-cell clones from three out of four donors responded to RTA epitopes within the domain D124-Q223, whereas one donor recognized the region I1-D124. The response to RTA peptides of T-cell lines and T-cell clones from two donors allowed the identification of immunogenic segments (D124-G140 and L161-T190) recognized in the context of different HLA-DRB1 alleles (HLA-DRB1*0801, and HLA-DRB1*11011 and B1*03011, respectively). The response to L161-T190 was investigated in greater detail. We found that the HLA-DRB1*03011 allele presents a minimal epitope represented by the sequence I175-Y183 of RTA, whereas the HLA-DRB1*11011 allele presents the minimal epitope M174-I184. RTA peptides and an I175A RTA point mutant allowed us to identify I175 as a crucial residue for the epitope(s) recognized by the two HLA-DRB1 alleles. Failure of T-cell clones to recognize ribosome inactivating proteins (RIPs) showing sequences similar but not identical to RTA further confirmed the role of I175 as a key residue for the epitope recognized in the context of HLA-DRB1*11011/03011 alleles.